(3GdMGhj aj Yde GdJOGhjs - (3fLe GdOjf eMehO Hf UGFf GdOjf EdjGS GdTjQGRjs; (3eMehO Hf UGFf GdOjf GdjGS GdTjQGRj, fLe GdOjf,J (B730 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdeGLO GdSHhM , NGdb GdLf hGdEfS, hQH GdedGFcI hGdQhM dCf TQa cd Yde hMSH ehVhYg hehVhY Yde GdWH HOf GdEfSGf hef GdHOjgjGJ Gf gPG GdehVhY ai YGde Gdchf s
(3BNQgG (B:s
(3hGeG dMe GdSehc GdeGdMI agh edWa ddCNdGW GdZdjXI hjfHZi Cf jNJGQ efg eG cGf dMekG djfkG ZjQ Sgd, hcdeG cGf CYJb cGf Cbhi s
(3QJHg Ydi NeS ebGdGJ aj GdYdd hGdMejGJs
(3hYdd GdCYVGA GdXGgQI hGdCOhjI GdeaQOI hGdCOhjI GdeQcHIs
(3hHYV GdChQGb HNW JYdjbs
(3eLdI eYgO GdeNWhWGJ(B311/5 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B80 s
Keywords: (3GdWHs